Employee Well-Being in the Digital Era: Exploring the Paradox of Flexibility and Burnout - Selfriyana Y. Tinake; Mutiara Nabila Sarah Dina Tamima (AIBPM Publisher, 2025)
Digital transformation has reshaped modern work by introducing greater flexibility while simultaneously creating new risks for employees’ psychological well-being. This study examines the paradox of digital flexibility and burnout using a library research approach with systematic narrative synthesis. Data were obtained from peer-reviewed journals indexed in Google Scholar, including major publishers such as Elsevier, Emerald, MDPI, and Springer. Guided by the Job Demands–Resources (JD-R) Model and the Conservation of Resources (COR) Theory, the findings show that digital flexibility can enhance autonomy, engagement, and efficiency. However, when work–life boundaries become blurred, this same flexibility may trigger technostress, emotional exhaustion, and reduced well-being. The review highlights that organizational support, empathetic leadership, and a strong psychosocial safety climate are crucial in preventing resource depletion and sustaining employee performance. Overall, the study concludes that achieving sustainable digital work requires aligning technological advancements with strategies that protect and promote employee psychological well-being